1992
DOI: 10.1017/s0003356100037284
|View full text |Cite
|
Sign up to set email alerts
|

Effects of genotype and stocking density on post-weaning daily gain and meat production per hectare in cattle

Abstract: With the objective of determining genetic × environmental interaction for beef production under direct grazing conditions, measured as both individual average daily gain (ADG) and per ha (PROD), 160 steers were utilized through 2 years, from two breeds of different growth potential, and four stocking rates (SR) tending to establish different nutritional environments. The breeds were Aberdeen Angus (A) and high-grade Limousin crossbred (L) and the SRs established were 2·25, 2·87, 3-50 and 4·13 steers per ha. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 8 publications
0
3
1
Order By: Relevance
“…These findings are in disagreement with those of other studies in which the relationship between ADG and stocking rate was linear (Mezzadra et al, 1992; Bransby et al, 1988; Hart, 1972; Bryant et al, 1965; Petersen et al, 1965; Riewe et al, 1963; Riewe, 1961), although Ashley (1993) and Oberholster (1990) also reported a quadratic relationship between ADG and stocking rate for annual ryegrass pastures and also for cereal rye ( Secale cereale L.).…”
Section: Resultscontrasting
confidence: 82%
“…These findings are in disagreement with those of other studies in which the relationship between ADG and stocking rate was linear (Mezzadra et al, 1992; Bransby et al, 1988; Hart, 1972; Bryant et al, 1965; Petersen et al, 1965; Riewe et al, 1963; Riewe, 1961), although Ashley (1993) and Oberholster (1990) also reported a quadratic relationship between ADG and stocking rate for annual ryegrass pastures and also for cereal rye ( Secale cereale L.).…”
Section: Resultscontrasting
confidence: 82%
“…If cattle grazing maintains patches of dense and nutritious forage and animals are able to compensate for possible constraints imposed by height to their rate of intake, similar individual animal gains should be expected under grazing pressure lower than 0.0016 animal units kg forage-l. Mean daily gains from September to December for 1987 (Mezzadra et al 1992), and 1988 (Mezzadra unpublished data) support this idea. In spite of large differences in forage availability between treatments, mean individual gains did not differ (p > 0.05) as stocking density increased in 1987 (0.540, 0.521, 0.530, 0.415 kg animal-l day-l) and in 1988 (0.491, 0.483, 0.553 and 0.438 kg animal-1 day-*).…”
Section: Discussionmentioning
confidence: 86%
“…Annual precipitation (959 and 859 mm in 1987 and 1988, respectively), as well as the amounts registered in the experimental period, were similar to the longterm median. The pasture had been under continuous grazing at 4 stocking densities from March to December since 1983 (Mezzadra et al 1992). It was divided by electric fences into 8 small paddocks of variable area according to the corresponding stocking density.…”
Section: Methodsmentioning
confidence: 99%
“…Earlier, GxE studies focusing on variation in nutritional environmental conditions have mainly been performed in controlled experiments (e.g. Mezzadra et al, 1992;Nugent et al, 1993;Jenkins & Ferrell, 1994;Baker et al, 2002;Durunna et al, 2011;McGregor et al, 2012). However, to investigate effects of GxE under commercial conditions, production results from commercial farms will have to be analysed.…”
Section: Introductionmentioning
confidence: 99%